(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research presents a critical dialectical study of some the theoretical models from the Islamic doctrine at the Mu’tazil and Ash’ayra. Therefore, the titles of its chapters did not exceed the circle of the so-called glorious word, that its subjects center on the divine self and its attributes, the creation of the Qur’an and the word of God, and the fatal and option… etc. In order to determine essence the demonstrations and arguments which used by theologians to defend of their opinions and doctrines, and that it did not exceed the framework of the dialectical arguments which its introductions begin from the religious text, and at best from the interpretations that this text may bear it, and does not exclude it from its sacred status and at the same time from the historical and social situation, that controls it a economic, social and political forces do not allow any interpretations or ideas that may contradict with its ideology.